Anesthesia outcomes of pregnant women with spinal diseases: a single-center case-series study - Adila Yakhup; Hisako Okada; Izumi Kawagoe; Hiroyuki Sumikura (JA Clinical Reports, 2023)
Abstract Background Neuraxial anesthesia is widely used as the most effective and standard method in obstetric anesthesia. However, there is a concern that neuraxial anesthesia may be technically difficult or ineffective in pregnant women with spinal disease. Therefore, this study aimed to investigate the implementation rate of neuraxial anesthesia among pregnant women with spinal diseases and their success rate at our institution. Methods The subjects of this study were pregnant patients who delivered at Juntendo University Nerima Hospital between April 2017 and December 2020. After obtaining ethics committee approval, data were collected from patients’ medical records. Results Of the 2682 pregnant women who delivered, 1550 underwent preanesthetic evaluation. There were 42 deliveries in 39 pregnant women with spinal diseases (1.7% of all pregnant women and 2.7% of those who underwent preanesthetic evaluation). The diagnoses included adolescent idiopathic scoliosis (51.3%), lumbar disc herniation (23.1%), and others. The mode of delivery was the elective cesarean section in 5 cases, emergent cesarean section in 8 cases, and vaginal delivery in 29 cases. Only one case required general anesthesia. Of the 38 cases of labor analgesia, the neuraxial block was inadequate in 3 cases (7.9%) and technically difficult in 3 cases (7.9%). However, the patients complained of no lower extremity neuropathy, infection, or inadvertent dural puncture. Discussion Neuraxial anesthesia was an option in most cases, even in pregnant women complicated with spinal disease, if an anesthesiologist’s plan before delivery after careful preanesthetic evaluation.